Increased Reaction Vessel Surface Area Decreases the Overall Mortality Rate of Rana catesbeiana Larvae during Chemically Induced Metamorphosis - Ashley K. Portell; Kayleigh E. Mackintosh; Solomon S. Wang; David W. Hoferer; Jeffrey O. Henderson (Journal of Zoological Research, 2024)
Stimulating precocious metamorphosis in anuran larvae is an important pedagogical tool for understanding vertebrate development. However, historically, artificially provoking metamorphosis by immersing tadpoles in exogenous inducing agents (e.g., thyroxine, and iodine) compromises the longevity of the experimental animals, resulting in up to 100% mortality within a week. In our undergraduate teaching lab, we house our experimental tadpoles in circular glass dishes having a surface area of 182 cm2. Over the past four academic years this lab was performed, we observed 100% mortality of experimental animals within 10, 12, or 15 days when treated with 10-5 M, 10-6 M, or 10-7 M thyroxine, respectively. Here, we investigated whether increasing the surface area to 413 cm2 using square glass dishes would reduce the mortality of the treated animals. Omnibus Kaplan-Meier survival analysis demonstrates a statistically significant decrease in mortality in tadpoles reared in the larger square dishes compared to those housed in the smaller round dishes (P < 0.05). However, increasing the surface area of our reaction vessels could not rescue survivability of those tadpoles immersed in thyroxine, but did increase survivability of control tadpoles maintained in pond water (P < 0.01), tadpoles subjected to iodine (P < 0.05) or treated with actinomycin D (P < 0.05). These data demonstrate that increasing available reaction vessel surface area reduces overall tadpole mortality during chemically modified metamorphosis in an undergraduate teaching lab setting.
Keywords: Rana catesbeiana